Non-pecuniary factors influencing diaspora homeland investment - Mohamed, Mohamed Abdullahi; Abdul Talib, Asmat Nizam (Springer, 2020)
This study attempts to provide a theoretical outline of the non-pecuniary factors influencing diaspora homeland investment. It presents the findings of previous scholars on non-pecuniary motivational factors that drive diaspora homeland investment decisions. Moreover, the study suggests other additional non-financial motives that nurture homeland investment decisions. To identify the non-monetary motivational factors influencing diaspora homeland investment, a comprehensive literature review on the perspectives of previous scholars was conducted. The study presents the analyses and findings of multiple scholars who studied diaspora investment motives. Although studies have suggested altruism, emotional satisfaction, and social status to be the primary motives, little is known about the non-economic motivations of diaspora homeland investment. Therefore, this study offers additional motivational factors to help broaden the understanding and provides an overview of the non-pecuniary factors that drive diaspora homeland investment intentions. It offers a comprehensive explanation of the topic, such as the background of diaspora investment, entrepreneurial activities, and general contributions to their home country. The study also presents recommendations for future studies.